2014
DOI: 10.1128/jcm.01766-13
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Culture Incubation Time in Orthopedic Device-Associated Infections: a Retrospective Analysis of Prolonged 14-Day Incubation

Abstract: Accurate diagnosis of orthopedic device-associated infections can be challenging. Culture of tissue biopsy specimens is often considered the gold standard; however, there is currently no consensus on the ideal incubation time for specimens. The aim of our study was to assess the yield of a 14-day incubation protocol for tissue biopsy specimens from revision surgery (joint replacements and internal fixation devices) in a general orthopedic and trauma surgery setting. Medical records were reviewed retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
(52 reference statements)
2
44
0
4
Order By: Relevance
“…Since recent studies recommended a prolonged cultivation time of up to 14 days for bone and joint infections (17,18), the diagnosis of P. acnes infections has become more frequently documented (19). In view of the high costs of a long incubation period, a recent study suggested that 7 days of incubation should be sufficient for accurately diagnosing orthopedic implant-associated infections (20). In this study, 96.6% of the infections were detected within 7 days.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Since recent studies recommended a prolonged cultivation time of up to 14 days for bone and joint infections (17,18), the diagnosis of P. acnes infections has become more frequently documented (19). In view of the high costs of a long incubation period, a recent study suggested that 7 days of incubation should be sufficient for accurately diagnosing orthopedic implant-associated infections (20). In this study, 96.6% of the infections were detected within 7 days.…”
mentioning
confidence: 75%
“…However, reducing the cultivation time to 7 days as proposed by previous studies (20,23) would have resulted in missing diagnosis in 15 patients (21.4%), suggesting that in patients with a high prevalence of P. acnes infections, a prolonged cultivation is crucial for detecting infections. This supports the results of a study, including fewer P. acnes infections (37 cases), …”
Section: Discussionmentioning
confidence: 99%
“…Butler-Wu et al suggested that for all periprosthetic specimens, minimal aerobic and anaerobic culture incubation periods of 13 days are highly recommended (29). However, Esteban et al and Schwotzer et al reported that compared with a 7-day incubation period, a 14-day incubation period does not add more positive results for sonicated orthopedic implants (28,33). In this meta-analysis, six studies were cultured anaerobically for 7 days and five studies were cultured anaerobically for 14 days.…”
mentioning
confidence: 97%
“…The duration of incubation is still controversial (28). Five-or 7-day incubations have often been reported (9,13,15,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation